2002
DOI: 10.1093/gerona/57.6.m392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Gender on Toe Flexor Muscle Strength

Abstract: Toe flexor muscle strength decreased significantly with age. This decrement underlies the known age-related reduction in the functional base of support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 6 publications
4
123
2
Order By: Relevance
“…Several researchers have reported associations between toe function, including toe flexor strength, and balance [1,4] and walking [2,3] in adults, as previously mentioned. Various reports have also indicated that reduced toe flexor strength is an important risk factor for falls among elderly individuals [16][17][18].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Several researchers have reported associations between toe function, including toe flexor strength, and balance [1,4] and walking [2,3] in adults, as previously mentioned. Various reports have also indicated that reduced toe flexor strength is an important risk factor for falls among elderly individuals [16][17][18].…”
Section: Introductionmentioning
confidence: 60%
“…Toe function influences physical performance among adults [1][2][3][4], with toe flexor strength decreasing with aging [1,5,6]. However, although toe flexor strength has been reported in various studies, it has not been measured using a standardized method, such as hand grip strength (HGS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using a pressure platform showed that older people had 32% less plantar flexion strength of the hallux and 27% less plantar flexion strength of the lesser toes than younger people 14) . Toe flexor muscle strength decreases significantly with age 26) . Previous studies have compared toe plantar flexor strength between older and younger persons.…”
Section: Discussionmentioning
confidence: 96%
“…Many researchers have tried to measure toe strength quantitatively. Endo et al 26) and Mickle et al 29) used a force plate to determine the ground reaction force, and Menz et al 14) and Nihal et al 30) used a pressure sensor and a paper-grip test to estimate toe strength. Other researchers have measured the total toe flexor muscle strength using a dynamometer 31,32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation